Moderation testing of dysfunctional audit behavior: internal auditor factors on audit quality - Yulianti Yulianti; Saifudin Saifudin; Ratna Novita Sari (Universitas Muhammadiyah Yogyakarta, Indonesia, 2024)
Research aims: The objective of this study is to examine the impact of auditor ethics, auditor professionalism, and dysfunctional audit behavior on the quality of audits, considering dysfunctional audit behavior as a potential moderating factor.Design/Methodology/Approach: The research utilized a sample of auditors from public accounting firms across Java, employing convenience sampling through smartPLS 3 software, with a total of 256 auditors participating. Research findings: The findings revealed that both auditor ethics and professionalism positively contribute to audit quality. In contrast, dysfunctional audit behavior shows no significant effect on audit quality, nor does it moderate the beneficial effects of auditor ethics and professionalism on audit quality. These results underscore the significance of auditor ethics and professionalism in enhancing the quality of financial report audits.Theoretical contribution/ Originality: The research outlined herein seeks to explore the impact of auditor ethics and professionalism on audit quality, considering the potential moderating effect of dysfunctional audit behavior.Practitioner/Policy implication: The study's implications are straightforward: Auditor ethics and professionalism are vital for the production of high-quality financial statement audits.Research limitation/Implication: While dysfunctional audit behavior appears to have no significant effect, it remains crucial for public accounting firms to monitor such behaviors. As a result, there is a need for public accounting firms to prioritize ongoing professional education to uphold and reinforce the standards of ethics and professionalism among auditors.